The effects of sevoflurane anesthesia on rat brain proteins: a proteomic time-course analysis - Kalenka, Armin; Hinkelbein, Jochen; Feldmann, Robert Enrico; Kuschinsky, Wolfgang; Waschke, Klaus F.; Maurer, Martin H. (Anesthesia & analgesia, 2007)
BACKGROUND: - Recent studies showed changes in cerebral protein expression up to 3 days after desflurane anesthesia in rats. In the present study, we investigated the existence of persisting changes on the proteome level after sevoflurane anesthesia that persisted for as long as 28 days after anesthesia. - METHODS: - Rats were anesthetized by spontaneous inhalation of 2.4% sevoflurane in air for 3 h. Animals (n = 6 for each group) were killed either directly, 72 h, or 28 days after anesthesia. Brains were removed and subjected to global protein expression profiling based on two-dimensional gel electrophoresis and mass spectrometry. Expression factors were compared to results from untreated conscious animals at each time point. Data were statistically analyzed by ANOVA (P < 0.01) and a cut of more than two-fold change in the expression factor. - RESULTS: - We found 11 protein spots differentially regulated directly after anesthesia. Seventeen proteins were differentially expressed 72 h after the anesthesia. Only one spot was differentially regulated 28 days after anesthesia. The plausible targets of these differentially regulated proteins can be attributed to synaptic vesicle handling and cell-cell communication. - CONCLUSIONS: - Sevoflurane induced relevant changes in protein expression profiles directly and 72 h after an anesthesia with 1 MAC. Twenty-eight days after the anesthesia, all proteins except one had returned to baseline levels of abundance.
Gesehen am 30.04.2021